RISK MANAGEMENT TO MINIMIZE CONSTRUCTION COMPANIES PROBLEMS - Faizal Addin Achmad (Jurnal Ekonomi, 2023)
The research objective is to explain and describe risk management in minimizing problems that occur in the construction companies. The research method was carried out qualitatively through a literature study approach with the development of theory from W. Brand William about risk management. Data collection techniques with documentation studies. Data processing techniques with condensation, data presentation, and drawing conclusions. Data validity technique with source triangulation. The results of the study show: (1) risk management is an effort made by the construction company to manage the risks that the construction company will face or is currently facing. (2) company problems are problems that arise as a result of discrepancies between processes and production results due to negligence in the utilization of the construction company resources. (3) company risk management steps: (a) risk identification, by analyzing and analyzing the characteristics of the problems faced by the company. (b) risk measurement, by measuring how big the problem will be at risk of causing harm to the construction company. (c) risk handling, namely efforts made by the company to accept, reject and fix existing problems with the aim of not causing fatal consequences for the construction company.